2008
DOI: 10.1099/vir.0.83658-0
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an infectious genotype 1b hepatitis C virus clone in human hepatocyte chimeric mice

Abstract: The establishment of clonal infection of hepatitis C virus (HCV) in a small-animal model is important for the analysis of HCV virology. A previous study developed models of molecularly cloned genotype 1a and 2a HCV infection using human hepatocyte-transplanted chimeric mice. This study developed a new model of molecularly cloned genotype 1b HCV infection. A full-length genotype 1b HCV genome, HCV-KT9, was cloned from a serum sample from a patient with severe acute hepatitis. The chimeric mice were inoculated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…This knowledge will further the development of intergenotypic recombinant cell culture systems containing yet undefined, minimal JFH1 elements that are critical for cell culture viability. Transfection of RNA transcripts of a genotype 1b cDNA clone into SCID-uPA mice engrafted with human hepatocytes was recently reported (34). In future studies, this model system might offer an alternative for studies of infectivity of cDNA clones in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…This knowledge will further the development of intergenotypic recombinant cell culture systems containing yet undefined, minimal JFH1 elements that are critical for cell culture viability. Transfection of RNA transcripts of a genotype 1b cDNA clone into SCID-uPA mice engrafted with human hepatocytes was recently reported (34). In future studies, this model system might offer an alternative for studies of infectivity of cDNA clones in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…Human hepatocyte-chimeric mice were intravenously injected with 50 μl of the human serum samples positive for HCV genotype 1b. The serum HCV RNA titer in human hepatocyte-chimeric mice was detected by nested PCR, as previously described (38,39). All animal protocols described in this study were performed in accordance with the guidelines and with approval of the Ethics Review Committee of Animal Experimentation of the Graduate School of Biomedical Sciences, Hiroshima University.…”
mentioning
confidence: 99%
“…RNA extraction and quantitation of HCV by real-time polymerase chain reaction (PCR) were performed as described previously [19]. Briefly, RNA was extracted from mice serum, livers, or cellular lysate using SepaGene RVR (Sankojunyaku, Tokyo, Japan) and reverse transcribed with a random hexamer and a reverse transcriptase (ReverTraAce; TOYOBO, Osaka, Japan) according to the instructions provided by the manufacturer.…”
Section: Quantitation Of Hcv Rna and Isg Mrnasmentioning
confidence: 99%
“…We and other groups had reported that this mouse model is useful for evaluating anti-HCV drugs such as IFN-a and anti-NS3 protease in vivo [17][18][19].…”
Section: Introductionmentioning
confidence: 98%